2014
DOI: 10.1039/c4cp01849d
|View full text |Cite
|
Sign up to set email alerts
|

Glass transition of poly(methyl methacrylate) nanospheres in aqueous dispersion

Abstract: Surfactant-free nanospheres and latex nanospheres of poly(methyl methacrylate) (PMMA) with diameter ranging from 20 to 220 nm are prepared by atom transfer radical polymerization (ATRP) in microemulsions and subsequent dialysis against deionized water. The glass transitions of these PMMA nanospheres are characterized using nano differential scanning calorimetry (nano-DSC) in aqueous dispersions. The glass transition temperature (Tg) of the surfactant-free PMMA nanospheres and nonionic PMMA latex nanospheres wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…76 The solid and dotted lines represent a best fit to the data for the template-supported PMMA tubes (t tube ≈ 2 R g + 9 nm) and the supported PDMS thin films (thickness ≈ 2 R g + 3 nm). T g,bulk = 9 K. The increase in T g with confinement is due to the attractive hydrogen-bonding interactions between the PMMA ester groups and the hydroxyl groups 8,27,40 on the template surface. These attractive interactions between the polymer and template surface result in decreased segmental mobility near the interface which can propagate into the nanotube interior.…”
Section: Design and Fabrication Of Supported Pmma Nanotubesmentioning
confidence: 99%
See 1 more Smart Citation
“…76 The solid and dotted lines represent a best fit to the data for the template-supported PMMA tubes (t tube ≈ 2 R g + 9 nm) and the supported PDMS thin films (thickness ≈ 2 R g + 3 nm). T g,bulk = 9 K. The increase in T g with confinement is due to the attractive hydrogen-bonding interactions between the PMMA ester groups and the hydroxyl groups 8,27,40 on the template surface. These attractive interactions between the polymer and template surface result in decreased segmental mobility near the interface which can propagate into the nanotube interior.…”
Section: Design and Fabrication Of Supported Pmma Nanotubesmentioning
confidence: 99%
“…Understanding the behavior of polymers in other geometries gives insight into the factors which affect T g and opens up the opportunity to better control or tune properties. Recent DSC studies on the T g -confinement behavior of aqueous dispersions of polymer nanospheres and quasi-nanospheres by Priestley and coworkers [37][38][39] and Feng et al 40,41 have reported that T g decreases with decreasing sphere size.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it is worth recalling that a number of polymer nanocomposites exhibit no experimentally detectable deviations from bulk T g . More recently, a number of works showed negative T g deviations in PS [38,51,193,194] and PMMA [50] nanospheres. This was the case for low silica contents in the polymer.…”
Section: Thermal Glass Transitionmentioning
confidence: 99%
“…This was the case for low silica contents in the polymer. In the works of Feng et al [50,51], it was demonstrated how the presence of a surfactant on the surface of the nanosphere and its nature (ionic or nonionic) has a crucial effect on the magnitude (if any) of deviations from bulk T g . Nanocomposites exhibiting no evidence of deviation from bulk T g are those of PVAc with neat silica [3] and poly(ether imide) (PEI) with carbon fiber [35].…”
Section: Thermal Glass Transitionmentioning
confidence: 99%
See 1 more Smart Citation